Some issues of interpretative reading in Czarist Russia - Karčiauskienė, M. (Psichologija, 1963)
The article analyses the issues of interpretative reading by disclosing the essence of interpretative reading and demonstrating how such reading was valued with a view to acquainting children with the surrounding reality. More attention is paid to such pedagogues who solved the problems of interpretative reading from the point of view of population positions and whose thoughts met the biggest repercussions in the theory and practice of Lithuanian schools.The founder of interpretative reading K. D. Ušinsky solved these issues by resorting to his own theory of primary education, which revealed the essence and purpose of the mother tongue at primary school. Ušinskiy analyzed the interpretative reading by associating it with the visual education: in the lessons of reading it is necessary not only to teach children to read, develop their thinking and language, but also to acquaint them with life by expanding their imagery and concepts.Ušinsky’s educational books “Native Word” and “Children’s World” and methodological guidebooks had an immense importance on improvement of primary education in Czarist Russia.Ušinsky’s followers (N. A. Korf, N. F. Bunakov, V. I. Bodolazov) developed his ideas paying special attention to application of interpretative reading, seeking to develop the primary education course and improve the methods. Following the populace principle formulated by Ušinsky, they invoked the nations subjugated by the Czarist Russia to fight for education in their own mother tongue.School reaction at the end of 19th century though suspended, failed to fully suppress the progressive thought. Significant role in this period was played by Tichomirov whose ideas found repercussions in Lithuania as well.At the end of 19th century to the beginning of 20th century the issues of the interpretative reading were solved on the one hand, under the influence of Ušinsky’s ideas, on the other hand, under the influence of Western pedagogical ideas, especially “activity” pedagogy.Accordingly, supporters of the idea to separate reading lessons from visual education appeared. They did not aim at acquainting children with life and elementary knowledge of geography and history by interpretative reading, nor were they any longer interested in questions of the methods of reading of subject-specific articles. During reading lessons they recommended usage of various creative activities for children, most often reduced to various kinds of motor activities instead of cultivating in children conscious reading skills and developing their verbal creative activities.Nevertheless, the most progressive Russian pedagogues managed to harmonize both Ušinsky’s and new ideas. Especially prominent in this area was Vachterov who continued to associate the interpretative reading lessons with investigation of the surrounding environment. In his opinion, visual education cannot be just optical and passive; it should be “material.” Opposite to Western ideas, Vachterov proposed to include the material learning into the system of interpretative reading.At the beginning of 20th century A. Popov’s “The Methods of the Russian Language” had direct influence on the development of the interpretative reading in Lithuania. Though affected by current ideas, A. Popov solved the interpretative reading problem in a narrow way; similar to Vachterov, he did not ignore the popular scientific articles according to which, alongside with direct cognition of the reality, a child must be taught to read popular scientific literature and thus expand the limits of his knowledge and imagery received in a direct way. A. Popov’s methods indicate how to apply drawing and other artistic activities to make lessons more efficient.Thus, disregarding that at the end of 19th century to the beginning of 20th the questions of interpretative reading instigated much polemic, and the very essence of this question was not fully disclosed, the most progressive pedagogues managed to use reading lessons by depolarizing school and life, by developing children’s activeness and expanding their world-views.All this affected Lithuanian schools not only during Czarist times, but also later on.
Keywords: history of pedagogy; reading; teaching of reading